The Relationship Of 'LILA' To The Incidence Of Anemia In Pregnant Women - Mona Lisa; Winnie Tunggal Mutika; Melda Maulia Herlisya; Ambariani Ambariani (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2023)
Anemia in pregnant women is the highest cause of maternal mortality, with 40% of pregnant women suffering from anemia. Maternal health during the pre-pregnancy period, during pregnancy, and during breastfeeding is a very critical period for the growth and development of the child. The first 1000 days of life is a sensitive period or "window of opportunity" Nutritional factors are direct factors that cause anemia during pregnancy, one of which is Chronic Energy Deficiency (CHD) by measuring Upper Arm Circumference (LILA). This study aims to determine the relationship of Upper Arm Circumference (LILA) to the incidence of anemia in pregnant women at Haryanti Depok Independent Midwife Practice (PMB). This study used a cross-sectional approach with a population of first trimester pregnant women in May 2019-May 2020 at PMB Haryanti Depok, totaling 118 pregnant women. Sampling using purposive sampling technique, namely pregnant women who meet the inclusion criteria of 105 pregnant women with complete medical record data. Data analysis used with chi-square test with sig <0.05. The results obtained as many as 68 pregnant women (64.8%) who experienced anemia, LILA measurements below normal limits as many as 62 pregnant women (59%). The statistical test results showed that there was a significant relationship between LILA and the incidence of anemia in pregnant women in the first trimester. Screening nutritional status by measuring LILA and checking hemoglobin levels plays an important role in preventing anemia, especially in pregnant women so that early treatment can be carried out.